Bonding to the Improved Disclosure Environment in the United States: Firms' Listing Choices and Their Capital Market Consequences - Hope, Ole-Kristian (Institutional Knowledge at Singapore Management University, 2007)
This paper examines whether the current reporting and disclosure requirements for foreign registrants in the United States affect foreign firms' decisions to list on a U.S. exchange. We find that while firms from a weak disclosure environment are more likely to cross-list and either trade over-the-counter or be placed privately among institutional investors, they are less likely to list on an exchange in which firms are required to comply with U.S. GAAP. This is consistent with the idea that the decrease in the potential private control benefits accruing to managers discourages them from listing on an organized exchange. We further conduct pricing tests to investigate whether the choice relating to the mode of listing has capital market consequences. These tests indicate that: (1) exchange-listing firms receive a higher valuation (i.e., Tobin's q) than non-exchange-listing firms; and (2) exchange-listing firms domiciled in a higher disclosure regime, who incur lower costs of U.S. GAAP compliance, generally receive a higher valuation than exchange-listing firms from a lower-disclosure regime. Overall, the lower tendency of firms domiciled in a lower disclosure regime to list on an organized exchange appears to be consistent with the smaller valuation benefit they receive from the listing.